Moral Injury and Suicide Ideation Among Israeli Combat Veterans: The Contribution of Self-Forgiveness and Perceived Social Support - Levi-Belz, Yossi (Journal of interpersonal violence, 2022)
Modern warfare within a civilian setting may expose combatants to severe moral challenges. Whereas most of these challenges are handled effectively, some potentially morally injurious events (PMIEs) may have deleterious psychological, spiritual, and interpersonal effects among them, which may increase the risk for suicide ideation and behaviors (SIB). In this study, we aimed to examine the protective role of self-forgiveness and perceived social support on the relationship between exposure to PMIEs and SIB among combat veterans. A sample of 191 Israeli combat veterans completed validated self-report questionnaires in a cross-sectional design study, tapping moral injury, SIB, perceived social support, and self-forgiveness. Veterans with a history of SIB revealed higher levels of exposure to PMIEs and lower levels of self-forgiveness and perceived social support than veterans with no SIB history. Moreover, beyond the contributions of the PMIE dimensions, significant contributions of self-forgiveness and perceived social support to current suicide ideation (SI) were found. Importantly, the moderating model indicated that higher social support moderated the link between PMIEs and current SI. Based on the current findings, it can be suggested that self-forgiveness and perceived social support are important contributors to lower SI levels among veterans with PMIEs. It can be further suggested that interpersonal support may help veterans develop a sense of belongingness and bonding, which is a plausible basis for diminishing the risk of SI following PMIE exposure.